ANDROID-BASED LECTURE ROOM SCHEDULING APPLICATION (CASE STUDY : STMIK PRINGSEWU CAMPUS) - Dela Jemirnia; Angger Purno Nugroho; Sucipto Sucipto (IJISCS (International Journal of Information System and Computer Science), 2018)
Technological developments are increasingly rapid and fast, especially and communication technology. For all fields, starting the fields of buying and selling, education, health, and others. The communication and information technology very helpful in various ways from the word of lecturers, campus staff, and students. STMIK Pringsewu still use manual, student still have to see schedule of waiting room of STMIK Pringsewu. Application development using php script. The method used to develop this system is by System Development Life Cycle approach with stages and design using Data Flow Diagram modelling. Based on the results of system testing, Application and Scheduling Applications are designed in accordance with the expected, it can be concluded that the application design courses and lecture room based on Android is work and function.